Antidiabetic Effect of Fermented Mesembryanthemum crystallinum L. in db/db Mice Involves Regulation of PI3K-Akt Pathway - Hye-Lin Kim; Yunu Jung; Hyo In Kim; Nak-Yun Sung; Min-Jee Kim; In-Jun Han; Geon Kim; Eun Yeong Nho; Sang-Yun Park; Yohan Han; Ji Hoon Jung; Dong-Sub Kim; et al. (Current Issues in Molecular Biology, 2023)
Type 2 diabetes (T2D) is a serious health issue with increasing incidences worldwide. However, current medications have limitations due to side effects such as decreased appetite, stomach pain, diarrhea, and extreme tiredness. Here, we report the effect of fermented ice plant (FMC) in the T2M mouse model of db/db mice. FMC showed a greater inhibition of lipid accumulation compared to unfermented ice plant extract. Two-week oral administration with FMC inhibited body weight gain, lowered fasting blood glucose, and improved glucose tolerance. Serum parameters related to T2D including insulin, glycosylated hemoglobin, adiponectin, and cholesterols were improved as well. Histological analysis confirmed the protective effect of FMC on pancreas and liver destruction. FMC treatment significantly increased the expression and phosphorylation of IRS-1, PI3K, and AKT. Additionally, AMP-activated protein kinase phosphorylation and nuclear factor erythroid 2–related factor 2 were also increased in the liver tissues of db/db mice treated with FMC. Overall, our results indicate the anti-diabetic effect of FMC; therefore, we suggest that FMC may be useful as a therapeutic agent for T2D.